Uji Efek Nefroprotektif Ekstrak Daun Kemangi (Ocimum Bacilicum L.) Terhadap Tikus Wistar Jantan Yang Diinduksi Aspirin - Rizkya Adinda Nasution; Asyrun Alkhairi Lubis; Novitaria Br Sembiring (STIKes Ibnu Sina Ajibarang, 2025)
The kidneys serve a vital function in maintaining homeostasis by filtering blood, excreting metabolic waste, and eliminating exogenous substances, including drugs and environmental toxins. However, prolonged or excessive exposure to certain chemicals, such as nonsteroidal anti-inflammatory drugs (NSAIDs) like aspirin, can result in nephrotoxicity and lead to significant renal damage. In the pursuit of alternative therapeutic agents with fewer side effects, natural compounds with antioxidant properties have gained increasing interest. Ocimum basilicum L., commonly known as sweet basil, is a medicinal plant traditionally used for various therapeutic purposes. Its leaves are rich in antioxidant compounds that are hypothesized to possess nephroprotective activity. This study aimed to investigate the protective effects of Ocimum basilicum leaf extract against aspirin-induced renal injury in experimental rats. The study involved dividing the rats into multiple groups: a control group, a group treated with aspirin only, and groups treated with aspirin followed by Ocimum basilicum leaf extract at different dosages (400, 600, and 800 mg/kg BW). Renal function was assessed via serum creatinine levels and histopathological analysis of kidney tissues. The results revealed that aspirin administration significantly increased serum creatinine levels and caused observable damage to kidney tissue, confirming nephrotoxicity. However, post-treatment with Ocimum basilicum extract, particularly at the highest dose of 800 mg/kg BW, markedly reduced serum creatinine levels and improved renal histological architecture. These findings indicate that Ocimum basilicum leaf extract has potential as a nephroprotective agent, capable of mitigating aspirin-induced kidney damage, likely through its antioxidant activity. Further research is warranted to explore its mechanism of action and potential clinical applications.